Efforts to Save the Universe: Muhammadiyah's Concern for the Environment - Harimurti, Shubhi Mahmashony; Alam, Shahbaz (Suhuf: International Journal of Islamic Studies, 2024)
Muhammadiyah as a part of the civilization has a responsibility to spread the mercy. The organization that founded by KH Ahmad Dahlan is not carrying the theme "Efforts to Save the Universe" for its 111th anniversary in 2023 without reason. This is because the universe is not fine. Especially the natural environment. The proof is the waste emergency, the prolonged impact of El Niño, forest fires, and the never-ending haze. These are the problems of this research. Collective efforts as the solutions are needed to resolve these problems. Muhammadiyah as a preaching movement of amar ma'ruf nahi munkar takes a role in caring for the environment. This research has some contributions. They are as a lesson learnt for another communities and the implementation of Fikih Biah. The purpose of this article is to analyze the realization of efforts to save the universe. The method used is literature research. Some literatures are used to reveal the role of Muhammadiyah to reach the good society (khairu ummah). Water jurisprudence, disaster jurisprudence, Global Forum for Climate Change, and a lot of communities empowering are the evidences of Muhammadiyah commitment to save this universe. The conclusion of this research that include in Muhammadiyah efforts is felt in adding environmental awareness, switching consumption behavior, and developing the quality of life of local socities.